New Media, Visual Consumption, and Scopophilia: The Use of YouTube by Male as Means of Escapism - Adde Oriza Rio (Atma Jaya Indonesia Catholic University, Jakarta, 2012)
Uses and gratiﬁ cation theory stated that audiences have media-related needs and they will use media actively and rationally to satisfy those needs. Does this also apply to new media? According to Ruggeiro (2000) new media has some characteristic that is interactivity, demassiﬁ cation, and asynchroniety. Lister et al. (2003) also found some characteristics of new media which are digital, interactive, hyper-textual, virtual, networked, and simulated. Therefore, conceptually, the ability of audiences to use new media to satisfy their needs will be greater because they can choose more freely what to do with new media in accordance with their needs. One of the audience’s motivations in media use is to escape from routine activities. Eye is the most used sense in new media consumption and Freud (1910) says that seeing activity will produce visual pleasure (scopophilia). However, Mulvey (1989) says that visuality is gendered so whenever a male use their eyes to see female body, they will do what is called by Mulvey as ‘male gaze’ which is seeing activity that put female as sexual object of male visuality. YouTube is a site that presents so many video contents that can be selected by the audiences to watch. This paper examines how ‘male gaze’ is performed as visual consumption on YouTube as means of escapism.